Предмет: Алгебра,
автор: Freiderich
Решите уравнения:
(3x-1)(3x+1)-2x(1+4x)=-2;
(2x+1)^2 + 2=2-6x^2
Ответы
Автор ответа:
1
(3x-1)(3x+1)-2x(1+4x)=-2
9х²-1-2х-8х²=-2
х²-2х+1=0
D=4-4=0
х=2/2=1
(2x+1)^2 + 2=2-6x^2
4х²+4х+1+2-2+6х²=0
10х²+4х+1=0
D=16-40<0, корней нет
9х²-1-2х-8х²=-2
х²-2х+1=0
D=4-4=0
х=2/2=1
(2x+1)^2 + 2=2-6x^2
4х²+4х+1+2-2+6х²=0
10х²+4х+1=0
D=16-40<0, корней нет
Freiderich:
Спасибо, снова.
Автор ответа:
0
1
9x²-1-2x-8x²+2=0
x²-2x+1=0
(x-1)²=0
x-1=0
x=1
2
4x²+4x+1+2-2+6x²=0
10x²+4x+1=0
D=16-40=-24<0
нет решения
9x²-1-2x-8x²+2=0
x²-2x+1=0
(x-1)²=0
x-1=0
x=1
2
4x²+4x+1+2-2+6x²=0
10x²+4x+1=0
D=16-40=-24<0
нет решения
Похожие вопросы
Предмет: Математика,
автор: kristinapronina12
Предмет: Английский язык,
автор: annavalion9
Предмет: Математика,
автор: Аноним
Предмет: Биология,
автор: ppul6272